ACTIVE POWER LOSSES IN LONG LINES DURING COORDINATED, LIMITING AND MALFUNCTION BEHAVIOR - Rimsky V.X.; Berzan V.P.; Patsiuk V.I.; Karcheva N.F.; Andros I.V. (Problems of the Regional Energetics, 2008)
Exact formulas for calculation of limiting values of transmitted capacity and efficiency of lines of a variable voltage with active loading on the reception end are resulted. Critical resistance and losses of capacity are determined depending on length Air-lines of an electricity transmission of a class of a voltage 500 … 750 kV. Emergency operation in the loaded electricity transmission is investigated.